2019
DOI: 10.3892/mmr.2019.10169
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous oestradiol benzoate induces male mice azoospermia through modulation of oxidative stress and testicular metabolic cooperation

Abstract: in most cases, exogenous oestradiol benzoate (eB) inhibits spermatogenesis, however, the mechanism underlying this process has not been fully elucidated. The present study investigated the effect of eB on redox equilibrium and glycometabolism in mouse testes. Male Kunming mice were divided into 3 groups and injected with 0, 5 and 10 mg/kg eB, respectively. Histological analysis revealed no sperm and far fewer spermatogenic cells in the testes of eB-treated mice. additionally, transmission electron microscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Azoospermia may be associated with oxidative damage. Indeed, Le mice was associated with oxidative stress [31]. Also subjects carrying heterozygous defects in the gene SECISBP2 have synthesis reduced of most of the 25 known human selenoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Azoospermia may be associated with oxidative damage. Indeed, Le mice was associated with oxidative stress [31]. Also subjects carrying heterozygous defects in the gene SECISBP2 have synthesis reduced of most of the 25 known human selenoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were incubted via primitive antibodies overnight at 4 °C with horseradish peroxidase-conjugated goat anti-rabbit IgG (H + L) secondary antibody, Alexa Fluor 594 (R37117) and immersed in ECL Plus Western Blotting detection reagent and displayed on Hyperfilm ECL (both from Amersham, Piscataway, NJ, USA). The band’s intensity was determined using Lab Works 4.5 software (UVP, Upland, CA, USA) [ 18 ]. The primary antibodies used for Western blotting were tubulin, HK2, PKM2, LDHA.…”
Section: Methodsmentioning
confidence: 99%
“…In detail, estrogens appear to modulate glucose transporter type 3 (Glut3) and Ldh mRNAs 108 . One study demonstrated that exogenous estradiol benzoate treatment in 4-week-old (prepubertal) rats caused subsequently azoospermia 109 . Furthermore, Glut3 mRNA was upregulated, while monocarboxylate transporter 2 (Mct2) and monocarboxylate transporter 4 (Mct4) mRNAs were downregulated 109 , suggesting that estrogens may promote the internalization of glucose but inhibit the export of lactate which is essential to support GCs.…”
Section: Obesity Influences Various Molecular Signaling Pathways In B...mentioning
confidence: 99%
“…One study demonstrated that exogenous estradiol benzoate treatment in 4-week-old (prepubertal) rats caused subsequently azoospermia 109 . Furthermore, Glut3 mRNA was upregulated, while monocarboxylate transporter 2 (Mct2) and monocarboxylate transporter 4 (Mct4) mRNAs were downregulated 109 , suggesting that estrogens may promote the internalization of glucose but inhibit the export of lactate which is essential to support GCs. Another study showed that both E 2 and bisphenol A increased oxidative stress and decreased insulin, Ir, Irs1, PI3K, and Glut2 protein levels in 3-month-old rat testis 110 .…”
Section: Obesity Influences Various Molecular Signaling Pathways In B...mentioning
confidence: 99%